Improving Students' Mathematics Communication Ability Through Geogebra: Peningkatan Kemampuan Komunikasi Matematika Melalui Geogebra - Istikomah, Endang; Zetriuslita, Zetriuslita; Nofriandi, Nofriandi (Pedagogia : Jurnal Pendidikan, 2021)
Student’s mathematical communication skills are low. Geogebra is a dynamic program with a variety of facilities that can be used as a medium of mathematics learning to visualize mathematical concepts and help to construct mathematical concepts. The purpose of this study was to determine the improvement of students’ matematical communication skills thorugh Geogebra. The research method use is quasi experiment. The sample used in this study was the second semester students of TA. 2018/2019. The reserach involved an experimental group and control group. The results showed that the value of sig. of 0,000 . The conclusion obtained is that the mathematical communication skills of student in the experimental class are better than increasing the mathematical communication skills of students in the control class.